Zemlyachestva and Regional Authorities in the Context of the Study of Migration from Dagestan to Western Siberia (Антропологический форум / Forum for Anthropology and Culture, 2021)
The article examines the peculiarities of interaction between Dagestani zemlyachestva (immigrant associations) and the regional authorities of both the host and originating communities, using as an example the associations for immigrants identifying with Dagestan in the towns of the Khanty-Mansi and Yamalo-Nenets Autonomous Okrugs. The article aims to describe the character of these interactions and to determine the current communicative strategies used by zemlyachestva in the context of the specific challenges that the regional authorities of KhMAO-Yugra, YaNAO and Dagestan present them with. The author examines the specifics of the contacts between the zemlyachestva and the originating community as represented by the Ministry of National Policy and Religious Affairs of the Republic of Dagestan and the Spiritual Directorate of the Muslims of Dagestan, and also with the authorities of the host community, primarily the municipal and regional administrations. In the latter case two behavioural strategies are identified, one directed towards co-operation with the authorities of the host community, and the other towards a closed kind of interaction within the framework of the zemlyachestvo. The article was written using material from the author’s fieldwork (interviews and observation) carried out in towns in both the regions and in Makhachkala in 2015, 2018 and 2019, and also using other sources (publications in the mass media and data on the official portals of the regions concerned).